Evaluation of durability of chemically modified natural feather shuttlecocks - Poon, Ryan Yung Chieh (2019)
Badminton is an international sport and is played by people all over the world. The history of badminton can be traced back to the ancient times of Greece and Egypt where players hit a feathered shuttlecock back and forth with small rackets. In modern times, the projectile used in badminton is called a shuttlecock. For approval of international play, it must be manufactured to strict dimensions specified by the Badminton World Federation (BWF). The material, dimensions and shape of the shuttlecock is extremely important as it would affect its flight characteristics and thereby affecting the fairness of game play. The shuttlecock must be made from natural and/or synthetic materials in which the flight characteristics should be similar to those produced by natural feathered shuttle with a cork base. Natural feathered shuttlecocks are known to be less durable. As the condition of the shuttlecock deteriorates, its flight characteristic also changes. Therefore, frequent replacement of shuttlecocks is needed which is not ideal as it incurs higher costs. This led to the creation of synthetic shuttlecocks which are more durable. However, the flight characteristics of synthetic shuttlecocks may differ greatly from natural feathered shuttlecocks which challenges the usage of synthetic shuttlecocks. In more recent times, a new solution to increase the durability of shuttlecocks have been proposed by Durabird, a start-up company from the Singapore. This solution includes chemically modifying the shuttlecock to improve the durability of it. The aim of this Final Year Project (FYP) is to investigate the durability of chemically treated shuttlecock. Four shuttlecocks will be used in this experiment and there are as follows: 1) Modified for long duration EG1130 Aeroplane shuttlecock 2) Modified for short duration EG1130 Aeroplane shuttlecock 3) Umodified EG1130 Aeroplane shuttlecock (Control) 4) Yonex AS50 EG1130 Aeroplane shuttlecock is a natural feathered shuttlecock currently available in the market and is chemically treated. The Yonex AS50, known to be the most widely used shuttlecock in tournaments is included in the experiment to serve as a comparison to a high-quality shuttlecock.